THE REPRESENTATION OF IDEAL DOCTOR-PATIENT COMMUNICATION IN THE KOREAN DRAMA ‘HOSPITAL PLAYLIST’ SEASON 1 - Muhammad Hanif Ahda; Bagas Indra Herlambang; Fenny Anita (Universitas Dharmawangsa Medan, 2026)
Communication between doctors and patients is a crucial aspect of healthcare services, as it influences understanding, trust and the success of the healing process. Popular media, such as television dramas, also shape public perceptions of how ideal communication in the medical world should occur. This study aims to examine the portrayal of ideal doctor-patient communication in the Korean drama *Hospital Playlist* Season 1. This research employs a qualitative approach with a descriptive research design. The subjects of this study are scenes and dialogues depicting interactions between doctors, patients and patients’ families in the drama. Data collection was carried out through observation and documentation of relevant scenes. Data processing techniques include data reduction, data display and drawing conclusions. Meanwhile, the data analysis technique employs Roland Barthes’ semiotic analysis, which focuses on three levels of meaning: denotation, connotation and myth. The results of the study show that at the denotative level, doctor-patient communication is represented as a hierarchical relationship, where doctors hold medical authority and power, whilst patients are positioned as recipients of medical instructions and decisions. At the connotative level, *Hospital Playlist* portrays doctor-patient communication as empathetic, dialogical and humanistic, as reflected in doctors’ attitudes towards understanding patients’ emotional states, employing persuasive approaches, and fostering a sense of security and trust. At the mythical level, the drama normalises the ideology of patient-centred care, which emphasises that the healing process is not solely focused on medical treatment but also on the quality of communication, interpersonal relationships and human values. In conclusion, *Hospital Playlist* Season 1 functions not only as entertainment but also as a representational medium that shapes the public’s understanding of ideal doctor-patient communication, emphasising the importance of empathy, openness and a patient-centred approach in medical practice.